2011
DOI: 10.1039/c0mb00282h
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cholesterol metabolism by gene expression profiling in the hippocampus

Abstract: An important part of the challenge of building models of biochemical reactions is determining reaction rate constants that transform substrates into products. We present a method to derive enzymatic kinetic values from mRNA expression levels for modeling biological networks without requiring further tuning. The core metabolic reactions of cholesterol in the brain, particularly in the hippocampus, were simulated. To build the model the baseline mRNA expression levels of genes involved in cholesterol metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…However, this may not be enough to conclude that the HD group had a cognitive deficit. Similar and more conclusive results confirmed our hypothesis in a study on both LDL receptor (LDLr) rodents and C57BL/6 6 Iran Red Crescent Med J. 2016; 18(12):e35677.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, this may not be enough to conclude that the HD group had a cognitive deficit. Similar and more conclusive results confirmed our hypothesis in a study on both LDL receptor (LDLr) rodents and C57BL/6 6 Iran Red Crescent Med J. 2016; 18(12):e35677.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies have also shown that APP processing by BACE1 is sensitive to cholesterol levels. Aβ deposits trigger several pathologic pathways involved in neuronal cell death (6). As the uptake of cholesterol from the circulating blood is prevented by an intact BBB, the brain is dependent on in situ synthesis of cholesterol (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram of the cholesterol synthesis and degradation pathways, and the reactions, used in this TTM TM Model are published [38]. Cholesterol synthesis I is found in adult brain; pathway III is prevalent during fetal and postnatal periods [7].…”
Section: B Aging Brain (Simulations Of Cholesterol Metabolism)mentioning
confidence: 99%
“…Our current Transcriptome To Metabolome TM Model simulates 16 core metabolic pathways that include 220 species (metabolites), 295 reactions, and over 250 genes. The gene expression levels from microarray data sets were used to derive the kinetic parameters for the reactions in the TTM TM Biosimulation Model [37,38] for each study group as per the original reports [1,2] . The secondary data sets, i.e., species levels and reaction flux values were exported by COPASI into tab-delimited text files.…”
Section: B Biological Simulations (Transcriptomic Data Mining)mentioning
confidence: 99%
See 1 more Smart Citation